2017
DOI: 10.1016/j.seppur.2017.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced removal of intracellular organic matters (IOM) from Microcystic aeruginosa by aluminum coagulation

Abstract: a b s t r a c tAlgal organic matter (AOM), especially intracellular organic matter (IOM), increases the levels of color and taste & odor, and promotes the formation of disinfection by-products (DBPs). This study isolated the IOM from Microcystis aeruginosa into the fractions with different molecular weight (MW), i.e., >100 kDa, 30-100 kDa, 10-30 kDa, and 3-10 kDa, and characterized them by techniques of dissolved organic carbon (DOC), UV absorbance and Excitation-emission matrix (EEM) fluorescence spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In case of Al anode, we obtained only a 40% DOC removal efficiency. Guo et al [40] reported a 38.7% DOC removal efficiency from the IOM of M. aeruginosa at 5 mg/L alum dosage. The charge neutralization process involves the elimination of AOM during coagulation owing to the occurrence of extremely negative charges on AOM [6].…”
Section: Discussionmentioning
confidence: 99%
“…In case of Al anode, we obtained only a 40% DOC removal efficiency. Guo et al [40] reported a 38.7% DOC removal efficiency from the IOM of M. aeruginosa at 5 mg/L alum dosage. The charge neutralization process involves the elimination of AOM during coagulation owing to the occurrence of extremely negative charges on AOM [6].…”
Section: Discussionmentioning
confidence: 99%
“…The binding sequence of functional groups in the CHPI fraction under Cu­(II) perturbation was as follows: amide II υ C–N → aryl υ C–H → polysaccharide ν C–O , aliphatic ν O–H → phenolic υ C–O, δ O–H , aliphatic δ C–H → aryl υ CC → ketone, amide, and carboxyl ν CO . Carboxyl groups usually show the fastest response to heavy metal ions and are concentrated in the CHPI fraction via the anion-exchange process. , However, amide groups in CHPI are the most sensitive moiety to Cu­(II) binding. The binding sequence of functional groups in the NHPI fractions was as follows: polysaccharide ν C–O , aliphatic ν O–H → ketone, and carboxyl ν CO → aryl υ CC → amide II υ C–N → phenolic υ C–O, δ O–H , and aliphatic δ C–H .…”
Section: Resultsmentioning
confidence: 99%
“…AOM from Microcystis sp. contains a mixture of compounds such as amino acids, peptides, polysaccharides, and proteins (Guo et al, 2017). Cyanobacterial cells were separated from the collected water samples by membrane filtration using a 0.45 μm (pore size) filter.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Microcystin-LR (MC-LR), one of the most toxic and frequently detected among microcystin congeners, is a hepatotoxin that can be lethal (Gutiérrez-Praena et al, 2012). In addition, cyanobacterial cells release algal organic matter (AOM) containing a wide spectrum of components such as amino acids, peptides, proteins, and polysaccharides (Guo et al, 2017). These are known to serve as precursors for disinfection byproducts (DBPs) (Hong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%